Heat transfer inhibiting sheet and battery pack
Patent Information
- Application Number
- CN202580025023.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-02-19
- Publication Date
- 2026-11-03
AI Technical Summary
In the existing technology, when using wet papermaking to manufacture thermal runaway suppression refractory sheets containing dry silica, the material cannot be evenly dispersed, resulting in reduced heat insulation performance; while dry forming method is prone to inorganic particle shedding, resulting in insufficient strength of the heat insulation sheet, which cannot effectively suppress the powder shedding caused by heat transfer and expansion of battery cells.
The heat transfer suppression sheet contains large-diameter inorganic particles and silica nanoparticles. By forming segregated and dispersed regions on the sheet surface, it improves heat insulation and compressive strength, suppresses powder shedding, and maintains heat insulation performance.
It effectively suppresses thermal runaway and flame spread of individual battery cells in the battery pack, maintains excellent heat insulation and strength, prevents the heat insulation sheet from falling off under compression, and improves the safety of the battery pack.
Smart Images

Figure CN123036706A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a heat transfer suppressor and a battery pack having the heat transfer suppressor. Background Technology
[0002] In recent years, from an environmental protection perspective, there has been active development of electric vehicles or hybrid vehicles powered by electric motors. These electric vehicles or hybrid vehicles are equipped with battery packs consisting of multiple battery cells connected in series or parallel to power the electric motor.
[0003] Furthermore, these battery cells primarily utilize lithium-ion secondary batteries, which offer higher capacity and output compared to lead-acid and nickel-metal hydride batteries. However, in cases of thermal runaway, such as a battery cell experiencing a rapid temperature rise and continued heating due to internal short circuits or overcharging, heat from the thermally runaway cell can propagate to adjacent cells, potentially causing thermal runaway in those cells as well.
[0004] As a method to suppress the propagation of heat from battery cells that have experienced thermal runaway, a common approach is to sandwich heat insulation sheets between the battery cells.
[0005] For example, Patent Document 1 discloses a thermal runaway-suppressing refractory sheet containing a substrate and an inorganic particle layer. In the aforementioned thermal runaway-suppressing refractory sheet, the substrate contains glass fiber, hygroscopic adhesive fiber, and fibrillated heat-resistant fiber, and the inorganic particle layer contains inorganic particles and an inorganic binder. Furthermore, the inorganic particle layer has a coating layer covering the surface of the fibers contained in the substrate, and a heat-insulating layer present on at least one surface of the substrate.
[0006] Patent document 1 describes that the above-mentioned thermal runaway suppression refractory sheet has the effects of fire resistance and heat insulation due to the presence of an inorganic particle layer as a coating layer and an inorganic particle layer as a shielding layer.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-96935 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] The thermal runaway suppression refractory sheet described in Patent Document 1 contains hygroscopic adhesive fibers, but these fibers need to be wetted during manufacturing to exhibit their adhesive properties. Therefore, when using hygroscopic adhesive fibers, the refractory sheet needs to be manufactured using a wet papermaking method.
[0012] However, when using dry silica or silica aerogel with low thermal conductivity to further improve insulation performance, there is a problem that refractory sheets cannot be manufactured using the wet formwork method. This is because if the material containing dry silica is formed into sheets using the wet formwork method, the dry silica will agglomerate due to water, increasing its thermal conductivity. Furthermore, silica aerogel is generally difficult to disperse in water; therefore, if the material containing silica aerogel is formed using the wet formwork method, a uniformly dispersed sheet cannot be obtained, leading to a reduction in quality.
[0013] On the other hand, when using inorganic particles such as dry-processed silica and silica aerogel to manufacture heat insulation sheets via dry molding, the inorganic particles may sometimes detach due to pressure, impact, etc. (hereinafter also referred to as powder shedding). Especially in recent years, the capacity of individual battery cells in battery packs has further increased, resulting in a higher expansion rate during charging and discharging. Therefore, when heat insulation sheets are placed between the battery cells in a battery pack, if the overall strength of the heat insulation sheet is low, the heat insulation sheet will be compressed and powder will shed due to the expansion of the battery cells during charging and discharging, thus reducing the heat insulation performance.
[0014] Therefore, there is a need to develop a heat transfer suppression sheet with even better heat insulation properties, which can suppress the performance degradation and powder shedding of battery cells caused by external compression, thereby suppressing the reduction in heat insulation.
[0015] The present invention was made in view of the above-mentioned problems, and its object is to provide a heat transfer suppressor sheet and a battery pack having the heat transfer suppressor sheet, the heat transfer suppressor sheet having excellent heat insulation properties, and being able to absorb the pressing pressure even when the heat transfer suppressor sheet is pressed, thereby suppressing powder shedding and maintaining excellent heat insulation properties.
[0016] Methods for solving problems
[0017] The above-mentioned objective of the present invention is achieved by the following [1] configuration of the heat transfer suppression sheet.
[0018] [1] A heat transfer inhibiting sheet, comprising heat-insulating particles and organic fibers, characterized in that, The heat-insulating particles comprise large-diameter inorganic particles with an average primary particle size of 0.1 μm or more and silica nanoparticles. A portion of the principal surface orthogonal to the thickness direction contains a first region where the large-diameter inorganic particles are segregated, and... In other parts of the main surface, there is a second region in which the large-diameter inorganic particles, the silica nanoparticles, and the organic fibers are dispersed.
[0019] Furthermore, preferred embodiments of the present invention regarding heat transfer suppression sheets relate to the following [2] to [8].
[0020] [2] According to the heat transfer suppression sheet of [1], the second region has a surface shape that is raised relative to the surface that constitutes the first region.
[0021] [3] The heat transfer inhibition sheet according to [1] or [2] is characterized in that the average primary particle size of the large-diameter inorganic particles is less than 50 μm.
[0022] [4] The heat transfer suppression sheet according to any one of [1] to [3] is characterized in that the large-diameter inorganic particles comprise at least one particle selected from metal oxides and metal carbides.
[0023] [5] The heat transfer suppression sheet according to any one of [1] to [3] is characterized in that the large-diameter inorganic particles comprise at least one particle selected from titanium dioxide, zircon, zircon, barium titanate, zinc oxide, aluminum oxide and silicon carbide.
[0024] [6] The heat transfer suppression sheet according to any one of [1] to [3] is characterized in that the large-diameter inorganic particles comprise titanium dioxide.
[0025] [7] The heat transfer suppression sheet according to any one of [1] to [6] is characterized in that the average primary particle size of the silicon dioxide nanoparticles is greater than 1 nm and less than 100 nm.
[0026] [8] The heat transfer inhibition sheet according to any one of [1] to [7] is characterized in that the silica nanoparticles comprise at least one particle selected from wet silica, dry silica and aerogel.
[0027] Furthermore, the above-mentioned objective of the present invention is achieved by the following configuration of the battery pack [9].
[0028] [9] A battery pack having a plurality of battery cells and a heat transfer suppressor sheet as described in any one of [1] to [8], wherein the plurality of battery cells are connected in series or in parallel.
[0029] Invention Effects
[0030] The heat transfer suppression sheet of the present invention exhibits excellent thermal insulation properties due to its large-diameter inorganic particles and silica nanoparticles. Furthermore, the presence of a first region where the large-diameter inorganic particles are agglomerated further suppresses heat transfer along the thickness direction of the sheet. Additionally, the presence of a second region where the large-diameter inorganic particles, silica nanoparticles, and organic fibers are dispersed mitigates pressure on the surface of the heat transfer suppression sheet, thus suppressing the reduction in thermal insulation performance caused by powder shedding.
[0031] According to the present invention, the battery pack, having a heat transfer suppression sheet as described above that has excellent heat insulation and heat insulation performance retention effect, can suppress thermal runaway of individual cells in the battery pack and the spread of flame to the outside of the battery casing. Attached Figure Description
[0032] Figure 1 This is a photographic illustration showing the surface of the heat transfer suppression sheet according to an embodiment of the present invention.
[0033] Figure 2 The accompanying photograph is a magnified view of a portion of the surface of the heat transfer suppression sheet according to an embodiment of the present invention.
[0034] Figure 3 This is a schematic diagram showing a cross-section of the heat transfer suppression sheet according to an embodiment of the present invention.
[0035] Figure 4 This is a schematic diagram illustrating the infrared reflection of large-diameter inorganic particles with a relatively small average primary particle size.
[0036] Figure 5 This is a schematic diagram illustrating the infrared reflection of large-diameter inorganic particles with a relatively large average primary particle size.
[0037] Figure 6 This is a schematic diagram showing a battery pack having a heat transfer suppression sheet according to an embodiment of the present invention. Detailed Implementation
[0038] The inventors conducted in-depth research and discovered that the aforementioned problems can be solved by having a first region on the surface of the heat transfer suppression sheet where large-diameter inorganic particles with an average primary particle size of a specified value or higher are agglomerated, and a second region where large-diameter inorganic particles, silica nanoparticles, and organic fibers are dispersed. Specifically, the first region on the surface of the heat transfer suppression sheet increases the probability of reflecting radiant heat, which accounts for a large portion of heat transfer, thus suppressing heat transfer. Furthermore, the second region, containing large-diameter inorganic particles, silica nanoparticles, and organic fibers, provides a buffering effect to the surface of the heat transfer suppression sheet, mitigating pressure on the surface and retaining the large-diameter inorganic particles and silica nanoparticles, resulting in excellent thermal insulation.
[0039] The following provides a detailed description of the heat transfer suppression sheet, its manufacturing method, and the battery pack according to embodiments of the present invention. It should be noted that the present invention is not limited to the embodiments described below, and can be implemented in any way without departing from the spirit of the invention.
[0040] [Heat Transfer Inhibition Tablets]
[0041] Figure 1 This is a photographic representation of the surface of the heat transfer suppression sheet according to an embodiment of the present invention. Figure 2 This is a photograph used as a substitute, showing a portion of it enlarged. Additionally, Figure 3 This is a schematic diagram showing a cross-section of the heat transfer suppression sheet according to an embodiment of the present invention.
[0042] like Figures 1-3 As shown, the heat transfer suppression sheet 10 of this embodiment contains heat-insulating particles 5 comprising large-diameter inorganic particles 1 and silica nanoparticles 2, and organic fibers 3. Furthermore, the heat transfer suppression sheet 10 has a first region 11 on a portion of its main surface 10a orthogonal to its thickness direction, where the large-diameter inorganic particles 1 are concentrated. Additionally, in the main surface 10a of the heat transfer suppression sheet 10, a second region 12 is formed in the region other than the first region 11, where the large-diameter inorganic particles 1, silica nanoparticles 2, and organic fibers are dispersed. Figure 1 In the diagram, the dark-colored area is designated as the first region 11, and the lighter-colored area compared to the first region 11 is designated as the second region 12.
[0043] like Figure 2As shown in the enlarged photograph, the main surface 10a of the heat transfer suppressor 10 has a sea-like portion formed by a first region 11 and an island-like portion formed by a second region 12. Furthermore, it has an island-like structure where the island-like portion is surrounded by the sea-like portion. In addition, in the main surface 10a of the heat transfer suppressor 10, the first region 11 has a mesh-like interconnected shape. The island-like portions formed by the second region 12 vary in size and shape, with most being curved in one or more places, and some having a narrowed shape. Corresponding to the shape characteristics of the second region 12, the mesh-like sea-like portion of the first region 11 also has various shapes that are curved or partially narrowed. The entire surface of the heat transfer suppressor 10 has these shape characteristics of the first region 11 and the second region 12, thereby further improving the effect of reflecting radiant heat and mitigating the effect of pressure through buffering.
[0044] In addition, such as Figure 3 As shown, the second region 12 has a surface shape that is raised compared to the surface constituting the first region 11. It should be noted that the large-diameter inorganic particles 1 not only agglomerate on the surface of the heat transfer suppressing sheet 10, but also agglomerate on the main surface 10a side in the thickness direction in the cross-sectional view of the heat transfer suppressing sheet 10.
[0045] One possible use of the heat transfer suppressor 10 is to sandwich it between multiple battery cells. Specific usage of the heat transfer suppressor 10 will be described later.
[0046] The effects of the heat transfer suppression sheet 10 constructed as described above will be explained below. Figure 4 This is a schematic diagram illustrating infrared reflection in the case of large-diameter inorganic particles with a relatively small average primary particle size. Additionally, Figure 5 This is a schematic diagram illustrating the infrared reflection of large-diameter inorganic particles with a relatively large average primary particle size. It should be noted that... Figure 4 and Figure 5 The illustration of organic fibers is omitted in the text.
[0047] Large-diameter inorganic particles can reflect most of the radiant heat that accounts for heat transfer, but the reflection is significantly affected by the infrared wavelength and the particle size. For example, when the particle size of large-diameter inorganic particle 1 is about 1.5 μm and smaller than the wavelength of the infrared radiation that needs to be suppressed, such as... Figure 4As shown, infrared radiation 4 passes through the large-diameter inorganic particles 1 and through the interior of the heat transfer suppression sheet 10. However, in this embodiment, due to the presence of a first region 11 where the large-diameter inorganic particles 1 are clustered, this first region 11 exhibits the behavior of inorganic particles with larger sizes than the original large-diameter inorganic particles 1. That is, the heat transfer suppression sheet 10 has inorganic particles with apparent larger sizes on at least a portion of its main surface 10a, increasing the probability of reflecting infrared radiation 4. Therefore, heat transfer within the heat transfer suppression sheet 10 can be suppressed, further improving thermal insulation.
[0048] In addition, such as Figure 5 As shown, when the particle size of the large-diameter inorganic particles 1 is, for example, about 5 μm, infrared rays 4 with the same wavelength as that particle size are reflected by the large-diameter inorganic particles 1, resulting in a heat transfer suppression effect. On the other hand, when the wavelength of the infrared rays 4 exceeds 5 μm, or when the infrared rays 4 pass through the dispersed large-diameter inorganic particles 1, the infrared rays 4 are reflected by the first region where the large-diameter inorganic particles 1 are concentrated. Therefore, with Figure 4 Similarly, as shown, heat transfer within the heat transfer suppression sheet 10 can be suppressed, further improving thermal insulation. That is, in this embodiment, regardless of the particle size of the large-diameter inorganic particles 1, heat transfer caused by infrared radiation 4 with a wide range of wavelengths can be suppressed.
[0049] It should be noted that regardless of which direction the heat (infrared 4) originates from the main surface of the heat transfer suppression sheet 10, it can be as... Figure 4 and Figure 5 As shown, heat is reflected. Therefore, for example, when a heat transfer suppression sheet 10 is sandwiched between multiple battery cells, heat transfer from one battery cell to other adjacent battery cells via the heat transfer suppression sheet 10 can be suppressed, and thermal runaway can be prevented.
[0050] Furthermore, in this embodiment, the island portion formed by the second region 12 has a raised surface shape compared to the sea portion formed by the first region 11. In this raised region (second region 12), the content of silica nanoparticles 2 and organic fibers 3 is higher than in the first region 11. Therefore, the second region 12 is softer than the first region and has excellent cushioning properties. Thus, when impact or pressure is applied to the heat transfer suppression sheet 10, the raised second region 12 absorbs and mitigates the impact and pressure, resulting in lower pressure on the first region 11 compared to when the second region 12 is not raised. As a result, it is possible to prevent large-diameter inorganic particles 1 and silica nanoparticles 2 from detaching from the main surface 10a of the heat transfer suppression sheet 10, and to suppress the reduction of heat insulation performance.
[0051] As described above, in this embodiment, the organic fiber 3 is also present inside the heat transfer suppression sheet 10, so the effect of maintaining the large-diameter inorganic particles 1 and the silica nanoparticles 2 can be fully achieved, and excellent sheet strength can be obtained.
[0052] The materials constituting the heat transfer suppression sheet of this embodiment will be described in detail below.
[0053] <Organic Fiber>
[0054] Organic fiber 3 imparts flexibility to the heat transfer suppression sheet 10 and improves its strength and shape. While single-component organic fibers can be used as the material for the organic fiber 3 in the heat transfer suppression sheet 10, core-sheath structured bonding fibers are preferred. The core-sheath structured bonding fiber has a core extending along the length of the fiber and a sheath formed to cover the outer peripheral surface of the core. Furthermore, the core is composed of a first organic material, and the sheath is composed of a second organic material, wherein the melting point of the first organic material is higher than that of the second organic material.
[0055] As the material for the organic fiber 3, whether using a single-component organic fiber or a core-sheath structure bonded fiber, during the manufacture of the heat transfer suppression sheet 10, a portion of the fiber surface is melted by heating, and then cooled to form a welded portion (not shown) around the organic fiber 3. The welded portion fuses the heat-insulating particles 5, comprising large-diameter inorganic particles 1 and silica nanoparticles 2, to the surface of the organic fiber 3, and also fuses the organic fibers 3 together. Therefore, by forming the welded portion, excellent sheet strength can be obtained.
[0056] When using core-sheath structured bonding fibers as the material, in the aforementioned heat transfer suppression sheet 10, the core is equivalent to the organic fiber 3. When manufacturing the heat transfer suppression sheet 10, if core-sheath structured bonding fibers are used, it is easy to form fiber bundles where adjacent bonding fibers are fused together, which can further improve the sheet strength. Furthermore, if core-sheath structured bonding fibers are used, the second organic material constituting the sheath melts and then solidifies again in a state containing the surrounding heat-insulating particles 5, thus improving the retention force of the heat-insulating particles 5.
[0057] (First Organic Material)
[0058] When using a core-sheath structured bonding fiber as the material for the organic fiber 3, there are no particular limitations as long as the melting point of the core, i.e., the first organic material constituting the organic fiber 3, is higher than that of the melting point of the sheath, i.e., the second organic material, which exists on the outer periphery of the organic fiber 3. Examples of the first organic material include at least one selected from polyethylene terephthalate, polypropylene, and nylon.
[0059] (Second Organic Material)
[0060] When using a core-sheath structure bonding fiber as the material of the organic fiber 3, the second organic material constituting the sheath is not particularly limited as long as its melting point is lower than that of the first organic material constituting the organic fiber 3. Examples of the second organic material include at least one selected from polyethylene terephthalate, polyethylene, polypropylene, and nylon.
[0061] It should be noted that the melting point of the second organic material is preferably 90°C or higher, more preferably 100°C or higher. Furthermore, the melting point of the second organic material is preferably 150°C or lower, more preferably 130°C or lower.
[0062] (Organic fiber content)
[0063] In this embodiment, if the content of organic fiber 3 in the heat transfer inhibition sheet 10 is properly controlled, the effects of improving the strength of the heat transfer inhibition sheet 10, maintaining the heat insulation particles 5, and imparting buffering properties to the heat transfer inhibition sheet 10 can be fully obtained.
[0064] The content of organic fiber 3 is preferably 2% by mass or more, more preferably 4% by mass or more, relative to the total mass of the heat transfer inhibiting sheet 10. In addition, if the content of organic fiber 3 is too high, the content of large-diameter inorganic particles 1 and silica nanoparticles 2 will be relatively reduced. Therefore, in order to obtain the desired heat insulation performance, the content of organic fiber is preferably 10% by mass or less, more preferably 8% by mass or less, relative to the total mass of the heat transfer inhibiting sheet 10.
[0065] (Fiber length of organic fibers)
[0066] There is no particular limitation on the fiber length of organic fiber 3. From the point of view of ensuring formability and processability, the average fiber length of organic fiber is preferably less than 10 mm.
[0067] On the other hand, from the viewpoint of improving the strength of the heat transfer suppression sheet, the average fiber length of the organic fiber 3 is preferably 0.5 mm or more.
[0068] <Insulating Granules>
[0069] The heat transfer suppression sheet 10 of this embodiment contains large-diameter inorganic particles with an average primary particle size of 0.1 μm or more and silica nanoparticles as heat-insulating particles 5. By using inorganic particles such as large-diameter inorganic particles 1 and silica nanoparticles 2, which have different heat transfer suppression effects, multi-stage cooling of the heating element is possible, and heat absorption can be achieved over a wider temperature range. The silica nanoparticles and large-diameter inorganic particles will be described in further detail below.
[0070] <Silica nanoparticles>
[0071] Silica is a component with high thermal insulation properties, and its nanoparticles have a low density, thus effectively suppressing conductive heat transfer. It should be noted that nanoparticles refer to spherical or near-spherical particles with an average primary diameter of less than 1 μm. When the heat transfer suppression sheet 10 contains silica nanoparticles 2, the pores are finely dispersed within the sheet, thus achieving excellent thermal insulation by suppressing convective heat transfer. Therefore, when using the battery in a typical room temperature range, it can suppress thermal conduction between adjacent nanoparticles.
[0072] Furthermore, when the heat transfer suppression sheet 10 contains silica nanoparticles 2, even when the heat transfer suppression sheet is compressed due to the expansion associated with the thermal runaway of the battery cells, resulting in an increase in internal density, the increase in conductive heat transfer can still be suppressed. This is believed to be because silica nanoparticles easily form fine voids between particles through electrostatic repulsion, resulting in a low packing density, thus filling the voids in a buffering manner.
[0073] Silica nanoparticles are not only highly insulating materials, but also, due to the small contact points between the particles, conduct less heat compared to using larger silica particles. Furthermore, the bulk density of typically obtained silica nanoparticles is 0.1 g / cm³. 3 Therefore, even if the battery cells disposed on both sides of the heat transfer suppression sheet undergo thermal expansion and exert large compressive stress on the heat transfer suppression sheet, the size (area) and number of contact points between the silica nanoparticles will not increase significantly, thus maintaining excellent thermal insulation. Examples of silica nanoparticles include wet silica, dry silica, and aerogel. It should be noted that the silica nanoparticles preferably contain at least one type of particle selected from wet silica, dry silica, and aerogel; alternatively, at least two types may be mixed. The silica nanoparticles particularly suitable for this embodiment will be described below.
[0074] Typically, wet-process silica particles aggregate, while dry-process silica particles can be dispersed. In the temperature range below 300°C, heat conduction is the primary mode of heat transfer; therefore, compared to wet-process silica, dry-process silica, which allows for particle dispersion, can achieve superior thermal insulation performance.
[0075] Furthermore, the heat transfer suppression sheet of this embodiment is preferably manufactured using a dry process to process the mixture containing the material into a sheet shape. Therefore, as silica nanoparticles, dry-processed silica, silica aerogel, or the like with low thermal conductivity is preferably used.
[0076] (Average primary particle size of silica nanoparticles: greater than 1 nm and less than 100 nm)
[0077] By limiting the average primary particle size of silica nanoparticles to a specified range, higher thermal insulation performance can be achieved. Specifically, when the average primary particle size of silica nanoparticles is set to be greater than 1 nm and less than 100 nm, especially in temperature regions below 500°C, convective and conductive heat transfer within the heat transfer suppression sheet can be suppressed, further improving thermal insulation performance. Furthermore, even under compressive stress, the voids remaining between the silica nanoparticles and the numerous contact points between particles can suppress conductive heat transfer, maintaining the thermal insulation performance of the heat transfer suppression sheet.
[0078] Furthermore, the average primary particle size of the silica nanoparticles is more preferably 2 nm or more, and even more preferably 3 nm or more. On the other hand, the average primary particle size of the silica nanoparticles is more preferably 50 nm or less, and even more preferably 20 nm or less.
[0079] It should be noted that, in this invention, the average primary particle size can be obtained by observing the particles under a microscope, comparing them with a standard scale, and taking the average value of any 10 particles.
[0080] Large-diameter inorganic particles
[0081] The heat transfer suppression sheet 10 includes the aforementioned silica nanoparticles 2, and also includes large-diameter inorganic particles 1 with an average primary particle size of 0.1 μm or more. The large-diameter inorganic particles 1 have a high refractive index, resulting in strong diffuse light reflection. Therefore, when the heat transfer suppression sheet 10 contains large-diameter inorganic particles 1, it can suppress radiative heat transfer, especially in high-temperature regions such as those experiencing abnormal heating. Preferably, the large-diameter inorganic particles include at least one particle selected from metal oxides and metal carbides. Furthermore, in addition to the aforementioned particles, the heat transfer suppression sheet 10 may also contain inorganic hydrate particles, microporous particles, hollow silica particles, or other inorganic microspheres, particles made of thermally expandable inorganic materials, or particles made of hydrous porous bodies. Hereinafter, metal oxides, metal carbides, inorganic hydrate particles, particles made of thermally expandable inorganic materials, particles made of hydrous porous bodies, and inorganic microspheres will be specifically described.
[0082] (Metal oxide particles)
[0083] Specifically, examples of metal oxide particles include titanium dioxide, zircon, zircon, barium titanate, zinc oxide, and aluminum oxide.
[0084] (Metal carbide particles)
[0085] Silicon carbide is an example of a metal carbide particle.
[0086] (Inorganic hydrate particles)
[0087] Inorganic hydrate particles undergo thermal decomposition when exposed to heat from a heating element and reaching temperatures above their thermal decomposition initiation temperature. This releases their own water of crystallization, lowering the temperature of the heating element and its surroundings, exhibiting a so-called "endothermic effect." Furthermore, after releasing the water of crystallization, they become porous, exhibiting a thermal insulation effect through numerous air pores.
[0088] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), zinc hydroxide (Zn(OH)2), iron hydroxide (Fe(OH)2), manganese hydroxide (Mn(OH)2), zirconium hydroxide (Zr(OH)2), and gallium hydroxide (Ga(OH)3).
[0089] For example, aluminum hydroxide contains approximately 35% water of crystallization, as shown in the formula below. Upon thermal decomposition, it releases this water of crystallization, exhibiting an endothermic effect. Furthermore, after releasing the water of crystallization, it transforms into a porous material called aluminum oxide (Al₂O₃), thus functioning as a thermal insulation material.
[0090] 2Al(OH)3→Al2O3+3H2O
[0091] It should be noted that, as described below, the heat transfer suppression sheet 10 of this embodiment is preferably located between battery cells, but in a battery cell that has experienced thermal runaway, the temperature can rise sharply to over 200°C and continue to rise to around 700°C. Therefore, the heat transfer suppression sheet 10 preferably contains inorganic hydrates with a thermal decomposition start temperature of 200°C or higher.
[0092] The thermal decomposition start temperatures of the inorganic hydrates listed above are approximately 200°C for aluminum hydroxide, approximately 330°C for magnesium hydroxide, approximately 580°C for calcium hydroxide, approximately 200°C for zinc hydroxide, approximately 350°C for iron hydroxide, approximately 300°C for manganese hydroxide, approximately 300°C for zirconium hydroxide, and approximately 300°C for gallium hydroxide. These temperatures roughly overlap with the temperature range of a single battery cell that experiences rapid temperature rise during thermal runaway, thus effectively suppressing temperature increases. Therefore, these inorganic hydrates can be considered preferred.
[0093] (Particles composed of thermally expanding inorganic materials)
[0094] Examples of thermally expandable inorganic materials include vermiculite, bentonite, mica, and perlite.
[0095] (Particles composed of hydrous porous bodies)
[0096] Specific examples of hydrous porous materials include zeolite, kaolinite, montmorillonite, acid clay, diatomite, mica, and vermiculite.
[0097] (Inorganic microspheres)
[0098] The heat transfer suppression sheet 10 of this embodiment may contain inorganic microspheres such as microporous particles and hollow silica particles as heat insulation particles 5.
[0099] When inorganic microspheres are included, the heat transfer suppression sheet 10 can suppress convective or conductive heat transfer in a temperature range below 500°C, thereby further improving the heat insulation performance of the heat transfer suppression sheet 10.
[0100] As inorganic microspheres, at least one selected from white sand microspheres (Shirasu balloon), silica microspheres, fly ash microspheres, barite microspheres, and glass microspheres can be used.
[0101] Among these large-diameter inorganic particles 1, at least one particle selected from metal oxide particles and metal carbide particles is preferably used. Specifically, as the large-diameter inorganic particles 1, at least one particle selected from titanium dioxide, zircon, zircon, barium titanate, zinc oxide, aluminum oxide, and silicon carbide is preferably used.
[0102] In particular, titanium dioxide has a high refractive index compared to other metal oxides. It is highly effective in diffusely reflecting light and shielding radiant heat in high-temperature regions above 500°C. Therefore, titanium dioxide is especially preferred as a large-diameter inorganic particle.
[0103] Thus, when the heat transfer suppression sheet 10 contains large-diameter inorganic particles 1 and small-diameter silica nanoparticles 2, the small-diameter silica nanoparticles 2 enter into the gaps between the large-diameter inorganic particles 1, thereby forming a denser structure and improving the heat transfer suppression effect.
[0104] (Average primary particle size of large-diameter inorganic particles)
[0105] By using large-diameter inorganic particles 1 with an average primary particle size of 0.1 μm or more, radiative heat transfer can be efficiently suppressed in the desired high-temperature region. It should be noted that when using large-diameter inorganic particles 1 with an average primary particle size of 1 μm or more, radiative heat transfer can be efficiently suppressed in high-temperature regions, for example, above 500°C. Therefore, the average primary particle size of the large-diameter inorganic particles 1 is set to 0.1 μm or more, preferably 1 μm or more, and more preferably 5 μm or more. On the other hand, the average primary particle size of the large-diameter inorganic particles 1 is preferably 50 μm or less, more preferably 30 μm or less, and further preferably 10 μm or less.
[0106] In this embodiment, the heat transfer suppression sheet 10 contains large-diameter inorganic particles 1 and silica nanoparticles 2. To obtain excellent heat insulation performance within a specified temperature range, the content of the large-diameter inorganic particles 1 and silica nanoparticles 2 is preferably appropriately adjusted. For example, to obtain excellent heat insulation performance within a temperature range below 300°C, the content of silica nanoparticles 2 is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, relative to the total mass of the heat-insulating particles. Furthermore, the content of silica nanoparticles 2 is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less, relative to the total mass of the heat-insulating particles.
[0107] On the other hand, in order to obtain excellent thermal insulation performance in a temperature range exceeding 300°C, the content of large-diameter inorganic particles 1 relative to the total mass of the thermal insulation particles is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more. Furthermore, the content of large-diameter inorganic particles 1 relative to the total mass of the thermal insulation particles is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0108] (Content of heat-insulating particles)
[0109] In this embodiment, if the total content of heat-insulating particles 5 in the heat transfer suppression sheet 10 is properly controlled, the heat insulation performance of the heat transfer suppression sheet 10 can be sufficiently ensured.
[0110] The total content of the heat-insulating particles 5 relative to the total mass of the heat transfer inhibiting sheet 10 is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 70% by mass or more. Furthermore, the total content of the heat-insulating particles 5 relative to the total mass of the heat transfer inhibiting sheet 10 is more preferably 75% by mass or more, even more preferably 80% by mass or more, and particularly preferably 85% by mass or more. On the other hand, if the total content of the heat-insulating particles 5 is too high, the content of the organic fibers 3 will be relatively reduced. Therefore, in order to fully obtain the sheet strength improvement effect brought about by the organic fibers 3, the total content of the heat-insulating particles 5 relative to the total mass of the heat transfer inhibiting sheet 10 is preferably 95% by mass or less, more preferably 90% by mass or less.
[0111] It should be noted that the content of heat-insulating particles 5 in the heat transfer inhibition sheet 10 can be calculated, for example, by heating the heat transfer inhibition sheet 10 at 800°C to decompose the organic components and then measuring the mass of the remaining portion.
[0112] Furthermore, in this embodiment, the total content of the heat-insulating particles 5 and the organic fibers 3 relative to the total mass of the heat transfer inhibiting sheet 10 is preferably 65% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more. Additionally, the total content of the heat-insulating particles 5 and the organic fibers 3 relative to the total mass of the heat transfer inhibiting sheet 10 is more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass or more. It should be noted that the total content of the heat-insulating particles 5 and the organic fibers 3 relative to the total mass of the heat transfer inhibiting sheet 10 can also be 100% by mass.
[0113] In the heat transfer suppression sheet 10 of this embodiment, in addition to the organic fiber 3 and the heat insulation particles 5 described above, it may also contain organic fibers, inorganic fibers, etc., made of organic materials different from the first organic material described above. When the heat transfer suppression sheet 10 contains inorganic fibers, the inorganic fibers preferably contained in this embodiment will be described as follows.
[0114] <Inorganic Fibers>
[0115] As inorganic fibers, a single inorganic fiber can be used, or two or more inorganic fibers can be used in combination. Examples of inorganic fibers include: silica fiber, alumina fiber, aluminosilicate fiber, zirconium oxide fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, potassium titanate whisker fiber and other ceramic-based fibers, glass fiber, glass wool, slag wool and other glass-based fibers, rock wool, basalt fiber, wollastonite fiber, mullite fiber and other mineral-based fibers, etc.
[0116] These inorganic fibers are preferred considering their heat resistance, strength, and availability. Among inorganic fibers, from an operational point of view, silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers are particularly preferred.
[0117] There are no particular limitations on the cross-sectional shape of inorganic fibers; examples include circular cross-sections, flat cross-sections, hollow cross-sections, polygonal cross-sections, and core-shaped cross-sections. Among these, fibers with irregular cross-sections such as hollow, flat, or polygonal cross-sections have slightly improved thermal insulation properties and are therefore preferred.
[0118] The preferred lower limit for the average fiber length of the inorganic fibers is 0.1 mm, and a more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit for the average fiber length of the inorganic fibers is 50 mm, and a more preferred upper limit is 10 mm. When the average fiber length of the inorganic fibers is less than 0.1 mm, it is difficult for the inorganic fibers to become entangled with each other, and the mechanical strength of the heat transfer suppression sheet 10 may be reduced. On the other hand, when it exceeds 50 mm, although a reinforcing effect can be obtained, the inorganic fibers cannot be tightly entangled with each other, or they are only curled as single inorganic fibers, which easily creates continuous gaps, and therefore may lead to a reduction in thermal insulation.
[0119] The preferred lower limit for the average fiber diameter of inorganic fibers is 1 μm, a more preferred lower limit is 2 μm, and a further preferred lower limit is 3 μm. Conversely, the preferred upper limit for the average fiber diameter of inorganic fibers is 15 μm, and a more preferred upper limit is 10 μm. When the average fiber diameter of inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may decrease. Furthermore, from the viewpoint of impact on human health, the average fiber diameter of inorganic fibers is preferably 3 μm or more. On the other hand, when the average fiber diameter of inorganic fibers is greater than 15 μm, the solid-state heat transfer using inorganic fibers as a medium increases, which may lead to a decrease in thermal insulation performance. Additionally, the formability and strength of the heat transfer suppression sheet may deteriorate.
[0120] (Inorganic fiber content)
[0121] In this embodiment, when the heat transfer inhibition sheet 10 contains inorganic fibers, the content of inorganic fibers relative to the total mass of the heat transfer inhibition sheet 10 is preferably 3% by mass or more and 15% by mass or less.
[0122] Furthermore, the content of inorganic fibers relative to the total mass of the heat transfer inhibiting sheet 10 is more preferably 5% by mass or more and 10% by mass or less. By setting such a content, the shape retention, pressure resistance, wind pressure resistance, and particle retention force provided by the inorganic fibers can be evenly expressed. In addition, by appropriately controlling the content of inorganic fibers, the organic fibers 3 and inorganic fibers intertwine to form a three-dimensional network, thereby further improving the effect of retaining the heat insulation particles and other compounding materials described later.
[0123] <Other ingredients>
[0124] Furthermore, the heat transfer suppressing sheet of this embodiment may further contain adhesive materials, colorants, etc., as needed. These components all contribute to achieving the purpose of enhancing the heat transfer suppressing sheet and improving its formability, and are preferably 10% or less by mass relative to the total mass of the heat transfer suppressing sheet.
[0125] It should be noted that when using core-sheath structured bonding fibers as the material for manufacturing the heat transfer suppression sheet, the sheath melts during manufacturing, leaving only the core in the form of organic fibers within the heat transfer suppression sheet. In this case, the content of the organic welded portion formed by melting the sheath is preferably 5% by mass or more and 15% by mass or less relative to the total mass of the heat transfer suppression sheet 10.
[0126] [Manufacturing method of heat transfer inhibition sheet]
[0127] Hereinafter, an example of the manufacturing method of the heat transfer suppression sheet 10 of this embodiment will be described.
[0128] For example, an organic fiber is mixed with insulating particles, including silica nanoparticles and large-diameter inorganic particles, in a predetermined ratio in a mixer such as a V-type mixer to prepare a mixture. Furthermore, as the organic fiber, a bonded fiber with a core-sheath structure having a core made of a first organic material and a sheath made of a second organic material is preferred. In this case, the melting point of the first organic material is higher than that of the second organic material.
[0129] The resulting mixture is then placed into a pre-designated mold, and vibration is applied to the mold to flatten the surface, thereby causing a portion of the large-diameter inorganic particles 1 with greater mass to move downwards. The resulting molded body is then pressurized using a press or similar device, and heated, thereby melting the sheath of the bonding fibers. The heated molded body is then cooled, and the molten sheath on the surface of the molded body solidifies, fusing the organic fibers 3 together with each other, and with the heat-insulating particles 5. Furthermore, depending on the type of large-diameter inorganic particles 1 selected, the second region 12 becomes a raised shape relative to the surface constituting the first region 11 due to the different shrinkage rates caused by heating and cooling. In this way, a heat transfer suppression sheet 10 with a first region containing a segregation of large-diameter inorganic particles 1 on a portion of the main surface can be manufactured.
[0130] In this embodiment, the heat transfer suppression sheet 10 is preferably manufactured using a dry process. When using a dry process, suitable dry-process silica nanoparticles are used as silica nanoparticles, and solvents such as water required for wet molding are not added to the mixture. However, when manufacturing the heat transfer suppression sheet 10, in order to prevent the powder such as dry-process silica nanoparticles from flying away and making the handling of raw materials difficult, a small amount of solvent such as water can be added within the dry process range. For example, by adding a small amount of solvent such as water to the mixture, the dispersion of heat-insulating particles during manufacturing can be suppressed.
[0131] According to the manufacturing method of this embodiment, since a first region with large-diameter inorganic particles 1 segregated is formed on a portion of the main surface 10a of the heat transfer suppression sheet 10, the large-diameter inorganic particles 1 and the first region 11 can reflect infrared rays 4 over a wide range of wavelengths, thus obtaining a heat transfer suppression sheet 10 with excellent heat insulation properties. Furthermore, since a second region with large-diameter inorganic particles 1, silica nanoparticles 2, and organic fibers 3 dispersed is formed on other portions of the main surface, a heat transfer suppression sheet 10 with excellent strength and heat insulation particle retention force can be manufactured. Moreover, when the second region 12 is formed in a shape that is raised compared to the surface constituting the first region 11, the pressing pressure on the first region 11 is further reduced, enabling the manufacture of a heat transfer suppression sheet 10 that maintains excellent heat insulation properties.
[0132] It should be noted that even when using organic fibers without a core-sheath structure as organic fibers 3, the effect of maintaining the heat-insulating particles 5 can still be achieved. In this case, as long as appropriate temperature management is implemented, only the surface of the organic fibers is melted and the heat-insulating particles are attached to the surface, or the organic fibers are fused together. Regardless of the type of organic fiber used, when the organic fibers 3 are fused together inside and on the surface of the heat transfer suppression sheet, they become a skeleton that increases the strength of the sheet, thus obtaining a heat transfer suppression sheet 10 with excellent strength.
[0133] Furthermore, as detailed later, the mixture may also contain binders such as hot-melt powder as a raw material for the heat transfer suppressing sheet 10. By appropriately adjusting the type and content of the binder in the mixture, the retention force of the heat-insulating particles 5 can be improved, further suppressing dust shedding.
[0134] In addition, to further suppress powder shedding, the surface of the heat transfer suppressing sheet 10 can be covered with a film or the like. Examples of polymer films include those made of polyimide, polycarbonate, PET, poly(p-phenylene sulfide), polyetherimide, cross-linked polyethylene, flame-retardant neoprene rubber, polyvinylidene fluoride, rigid vinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PVC, flame-retardant PET, polystyrene, polyethersulfone, polyamide-imide, polyacrylonitrile, polyethylene, polypropylene, and polyamide. Furthermore, there are no particular limitations on the method of covering the surface of the heat transfer suppressing sheet 10 with a film; methods such as bonding with adhesives, wrapping the heat transfer suppressing sheet 10 in a film, or storing the heat transfer suppressing sheet 10 in a bag-like film are also possible.
[0135] Next, the preferred organic fibers and heating conditions used in the manufacturing method of the heat transfer inhibition sheet of this embodiment will be described.
[0136] <Organic Fiber>
[0137] In this embodiment, when using organic fibers with a core-sheath structure, there are no particular limitations as long as the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath. The first organic material forming the core can be selected from at least one of polyethylene terephthalate, polypropylene, and nylon. Furthermore, the second organic material forming the sheath can be selected from at least one of polyethylene terephthalate, polyethylene, polypropylene, and nylon.
[0138] When the melting point of the first organic material constituting the core is sufficiently higher than that of the second organic material constituting the sheath, the temperature setting margin in the heating process can be expanded, and the temperature setting for obtaining the desired structure can be more easily achieved. For example, it is preferable that the melting point of the first organic material is 60°C or more higher than that of the second organic material, more preferably 70°C or more higher, and even more preferably 80°C or more higher.
[0139] Furthermore, the aforementioned organic fibers with core-sheath structures are generally commercially available, and the materials constituting the core and sheath can be the same or different. Examples of organic fibers with the same core and sheath material but different melting points include organic fibers with a core and sheath made of polyethylene terephthalate, organic fibers made of polypropylene, and organic fibers made of nylon. Examples of organic fibers with different core and sheath materials include organic fibers with a core made of polyethylene terephthalate and a sheath made of polyethylene; and organic fibers with a core made of polypropylene and a sheath made of polyethylene.
[0140] In this embodiment, the melting point of the second organic material constituting the sheath of the organic fiber represents the melting temperature at which the second organic material begins to melt and deform, but softening accompanying shape change is also considered a type of melting and deformation. The melting point of the sheath of the bonded fiber can be determined, for example, by the following method.
[0141] The organic fiber, which is the object of the test, is placed in contact with glass fiber, which has a higher melting point. It is heated from room temperature to, for example, 200°C at a heating rate of 5°C / min, and then cooled to room temperature. If the surface of the organic fiber melts and deforms, fusing with the glass fiber at the point of contact, or if the cross-sectional shape of the organic fiber changes, it can be determined that the melting point of the second organic material constituting the sheath is below 200°C. In this embodiment, by varying the heating temperature and observing the fusion state of the cooled organic fiber and glass fiber or the cross-sectional shape of the organic fiber using the above method, the melting point of the second organic material constituting the sheath can be determined.
[0142] (Organic fiber content)
[0143] In this embodiment, when using organic fibers with a core-sheath structure, if the content of organic fibers in the mixture is properly controlled, excellent thermal insulation performance and retention of thermal insulation particles can be obtained, as well as excellent sheet strength.
[0144] The content of organic fibers relative to the total mass of the mixture is preferably 5% by mass or more, more preferably 10% by mass or more. Furthermore, if the content of organic fibers is too high, the content of insulating particles will be relatively reduced. Therefore, in order to obtain the desired insulating performance, the content of organic fibers relative to the total mass of the mixture is preferably 25% by mass or less, more preferably 20% by mass or less.
[0145] <Hot Melt Powder>
[0146] In this embodiment, in addition to the aforementioned organic fibers and heat-insulating particles, the mixture may also contain hot-melt powder. The hot-melt powder is, for example, a powder containing a third organic material different from the first and second organic materials and possessing the property of melting upon heating. By including the hot-melt powder in the mixture and heating it, the hot-melt powder melts, and upon cooling, it solidifies while still containing the surrounding heat-insulating particles. Therefore, it is possible to further suppress the heat-insulating particles from detaching from the heat transfer suppression sheet 10.
[0147] As a hot-melt powder, various hot-melt powders with different melting points can be cited. Considering the melting points of the core and sheath of the bonding fiber used, a hot-melt powder with an appropriate melting point can be selected. Specifically, as long as the melting point of the third organic material constituting the hot-melt powder is lower than the melting point of the first organic material constituting the aforementioned organic fiber, the heating temperature for melting the sheath and hot-melt powder while retaining the core can be set. For example, when the melting point of the hot-melt powder is below the melting point of the sheath, the heating temperature during manufacturing can be set between the melting points of the core and the sheath, thus making it easier to set the heating temperature.
[0148] On the other hand, the type of hot-melt powder used can also be selected such that its melting point is between the melting point of the core and the melting point of the sheath. When using a hot-melt powder with such a melting point, after both the sheath and the hot-melt powder melt, upon cooling and solidification, the hot-melt powder existing in the gaps between the organic fiber (core) 3 and the surrounding molten sheath and insulating particles solidifies first. As a result, the position of the organic fiber 3 can be fixed, and then the molten sheath fuses with the organic fiber, thereby easily forming a three-dimensional skeleton. Therefore, the overall strength of the sheet can be further improved.
[0149] When the melting point of the third organic material constituting the hot-melt powder is sufficiently lower than the melting point of the first organic material constituting the core, the temperature setting margin in the heating process can be expanded, and the temperature setting for obtaining the desired structure can be more easily achieved. For example, it is preferable that the melting point of the first organic material is 60°C or more higher than the melting point of the third organic material, more preferably 70°C or more higher, and even more preferably 80°C or more higher.
[0150] Furthermore, the melting point of the hot-melt powder (third organic material) is preferably 80°C or higher, more preferably 90°C or higher. Additionally, the melting point of the hot-melt powder (third organic material) is preferably 180°C or lower, more preferably 150°C or lower. Examples of components constituting the hot-melt powder include polyethylene, polyester, polyamide, and ethylene vinyl acetate.
[0151] (Content of hot melt powder)
[0152] When the mixture contains hot-melt powder to suppress the shedding of the insulating particles 5, even a trace amount can achieve the effect of suppressing powder shedding. Therefore, the content of hot-melt powder relative to the total mass of the mixture is preferably 0.5% by mass or more, and more preferably 1% by mass or more.
[0153] On the other hand, if the content of hot melt powder is increased, the content of insulating particles 5 and the like will be relatively reduced. Therefore, in order to obtain the desired insulating performance, the content of hot melt powder relative to the total mass of the mixture is preferably 5% by mass or less, and more preferably 4% by mass or less.
[0154] <Heating conditions>
[0155] As a process for processing the above mixture into a sheet, examples include pressing the mixture and heating the mixture. When using organic fibers with a core-sheath structure as the material for the heat transfer suppressing sheet 10, the heating temperature in the heating process is preferably set to a temperature higher than the melting point of the second organic material constituting the sheath and lower than the melting point of the first organic material constituting the core. By setting the heating temperature to such a level, as described above, the strength of the sheet can be ensured by the core on either the surface side or the center side of the sheet, and the heat-insulating particles 5 can be retained by the welded sheath.
[0156] Specifically, the heating temperature in the heating process is preferably set to be at least 10°C higher than the melting point of the second organic material constituting the sheath, and more preferably at least 20°C higher. On the other hand, the heating temperature is preferably set to be at least 10°C lower than the melting point of the first organic material constituting the core, and more preferably at least 20°C lower.
[0157] There is no particular limitation on the heating time, but it is preferable to set a heating time that allows the sheath to melt sufficiently. For example, it can be set to a time of 3 minutes or more but less than 15 minutes.
[0158] When the material includes hot-melt powder as the heat transfer suppressor, the heating temperature in the heating process is preferably set to be at least 10°C higher than the higher of the melting point of the second organic material constituting the sheath and the melting point of the third organic material constituting the hot-melt powder, more preferably at least 20°C higher. On the other hand, the heating temperature is preferably set to be at least 10°C lower than the melting point of the first organic material constituting the core, more preferably at least 20°C lower. By setting the heating temperature to such a level, a robust framework can be formed, the strength of the sheet can be further improved, and the shedding of the heat-insulating particles 5 can be prevented.
[0159] <Thickness of the heat transfer inhibition sheet>
[0160] The thickness of the heat transfer suppression sheet 10 in this embodiment is not particularly limited, but is preferably 0.05 mm or more and 10 mm or less. When the thickness is 0.05 mm or more, sufficient compressive strength can be obtained. On the other hand, when the thickness is 10 mm or less, good heat insulation properties of the heat transfer suppression sheet 10 can be obtained.
[0161] [Battery Pack]
[0162] Figure 6 This is a schematic diagram illustrating a battery pack having a heat transfer suppression sheet according to an embodiment of the present invention. Figure 6 As shown, the battery pack 100 has a plurality of battery cells 20a, 20b, 20c and a heat transfer suppression sheet 10 of this embodiment, and these plurality of battery cells 20a, 20b, 20c are connected in series or in parallel.
[0163] Specifically, the heat transfer suppression sheet 10 is located between battery cells 20a and 20b, and between battery cells 20b and 20c. Furthermore, multiple battery cells 20a, 20b, and 20c are housed in the battery casing 30 in series or parallel connection (connection configurations are not shown in the diagram) to form the battery pack 100. Additionally, battery cells 20a, 20b, and 20c are preferably lithium-ion secondary batteries, but are not particularly limited to this, and other types of secondary batteries can also be used.
[0164] In addition, regarding the heat transfer inhibition sheet 10, as described above.
[0165] In the battery pack 100 configured in this way, even when a certain battery cell 20a reaches a high temperature, the heat transfer suppression sheet 10 with excellent heat transfer suppression effect is present between it and the battery cell 20b, thus suppressing the propagation of heat to the battery cell 20b.
[0166] Furthermore, the heat transfer suppression sheet 10 of this embodiment has high strength and the ability to absorb impact and resist pressure. Therefore, even during the charging and discharging of battery cells 20a, 20b, and 20c, it can suppress the thermal expansion of these battery cells. Thus, it can ensure the distance between battery cells, maintain excellent heat insulation performance, and prevent thermal runaway of battery cells. In addition, since it has the effect of suppressing powder shedding, it can be easily processed.
[0167] It should be noted that the battery pack 100 in this embodiment is not limited to... Figure 6 The illustrated battery pack. For example, the heat transfer suppression sheet 10 can be disposed not only between battery cells 20a and 20b, and between battery cells 20b and 20c, but also between battery cells 20a, 20b, and 20c and the battery casing 30, or attached to the inner surface of the battery casing 30.
[0168] In the battery pack 100 configured in this way, in the event of a fire in a single battery cell, the spread of flames to the outside of the battery casing 30 can be suppressed.
[0169] For example, the battery pack 100 of this embodiment is sometimes used in electric vehicles (EVs) and is installed under the floor of the passenger. In this case, even if a single battery cell catches fire, the safety of the passenger can be ensured.
[0170] In addition, the heat transfer suppression sheet 10 can be placed between each battery cell, or it can be placed between the battery cells 20a, 20b, 20c and the battery casing 30. Therefore, there is no need to make fireproof materials, etc., and a safe battery pack 100 can be easily constructed at low cost.
[0171] In the battery pack of this embodiment, the heat transfer suppression sheet 10 disposed between the battery cells 20a, 20b, 20c and the battery casing 30 can be in contact with the battery cells or may have a gap. For example, when the heat transfer suppression sheet 10 is in contact with the battery cells 20a, 20b, 20c, the heat transfer suppression sheet 10 is fixed between the battery cells, thus preventing performance degradation caused by misalignment. Furthermore, when there is a gap between the heat transfer suppression sheet 10 and the battery cells 20a, 20b, 20c, deformation of the battery cells can be allowed even if the temperature of any one of the battery cells rises or its volume expands.
[0172] It should be noted that the heat transfer suppression sheet 10 of this embodiment can be manufactured into various shapes using its manufacturing method. Therefore, it is not affected by the shape of the battery cells 20a, 20b, 20c and the battery casing 30, and can be used for batteries of any shape. Specifically, in addition to prismatic batteries, it can also be applied to cylindrical batteries, flat batteries, etc.
[0173] Various embodiments have been described above with reference to the accompanying drawings, but the present invention is not limited to these examples. It should be understood that various modifications or alterations will be readily apparent to those skilled in the art within the scope of the claims, and these modifications also fall within the technical scope of the present invention. Furthermore, the constituent elements of the above embodiments can be combined arbitrarily without departing from the spirit of the invention.
[0174] Furthermore, this application is based on Japanese Patent Application No. 2024-056366, filed on March 29, 2024, the contents of which are incorporated herein by reference.
[0175] Explanation of reference numerals in the attached figures
[0176] 1. Large-diameter inorganic particles
[0177] 2. Silica nanoparticles
[0178] 3. Organic Fibers
[0179] 4. Infrared
[0180] 5. Thermal insulation particles
[0181] 10 Heat transfer inhibitor tablets
[0182] 11 First District
[0183] 12 Second Region
[0184] 20a, 20b, and 20c battery cells
[0185] 30 Battery casing
[0186] 100 battery pack.
Claims
1. A heat transfer inhibiting sheet, comprising heat-insulating particles and organic fibers, characterized in that, The heat-insulating particles comprise large-diameter inorganic particles with an average primary particle size of 0.1 μm or more and silica nanoparticles. A portion of the principal surface orthogonal to the thickness direction contains a first region where the large-diameter inorganic particles are segregated, and... In other parts of the main surface, there is a second region in which the large-diameter inorganic particles, the silica nanoparticles, and the organic fibers are dispersed.
2. The heat transfer suppression sheet according to claim 1, characterized in that, The second region has a surface shape that is raised relative to the surface that constitutes the first region.
3. The heat transfer suppression sheet according to claim 1, characterized in that, The average primary particle size of the large-diameter inorganic particles is less than 50 μm.
4. The heat transfer suppression sheet according to claim 1, characterized in that, The large-diameter inorganic particles comprise at least one particle selected from metal oxides and metal carbides.
5. The heat transfer suppression sheet according to claim 1, characterized in that, The large-diameter inorganic particles comprise at least one particle selected from titanium dioxide, zircon, zircon, barium titanate, zinc oxide, aluminum oxide, and silicon carbide.
6. The heat transfer suppression sheet according to claim 1, characterized in that, The large-diameter inorganic particles contain titanium dioxide.
7. The heat transfer suppression sheet according to claim 1, characterized in that, The average primary particle size of the silica nanoparticles is greater than 1 nm and less than 100 nm.
8. The heat transfer suppression sheet according to claim 1, characterized in that, The silica nanoparticles comprise at least one type of particle selected from wet silica, dry silica, and aerogel.
9. A battery pack having a plurality of battery cells and a heat transfer suppressor sheet according to any one of claims 1 to 8, wherein the plurality of battery cells are connected in series or in parallel.
Citation Information
Patent Citations
Thermal runaway suppression fireproof sheet
JP2021096935A
Information processing device, information processing method, and computer program
JP2024056366A
